Removal of Listeria monocytogenes Biofilm with Some Local Plant Extracts of Kurdistan Region - Mohammed, Srwa A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
The results of removing or reducing biofilm were determined using subinhibitory concentrations (SICs) of some local plants in the flora of Kurdistan region of Iraq on biofilm production in Listeria monocytogenes. About 10–500 µg/ml of the plant extracts were used against growth and biofilm production in tissue culture plates which were measured spectroscopically. The SIC effects of each of Eugenia caryophyllata (Clove) and Rhus glabra (Sumac) have significantly affected on planktonic cells and reduced sessile cells or biofilm formation in L. monocytogenes. Remarkably, the data showed strong biofilm reduction under synergistically effect of the plant extract mixed with the antimicrobial agents in multidrugresistant L. monocytogenes. Whereas the SIC some of other plant extracts such as Salix candida and pomegranate (Punica granatum) have significantly enhanced biofilm expression in L. monocytogenes, but the use of these extracts synergistically with some antibiotics also resulted in inhibition of biofilm in comparison to merely use of either the extracts or antibiotics. The result of statistical analyses shows that P > 0.05. The results showed that the combination of plant extract with antibiotic together has more effect than using plant merely.